Design and Fabrication of “360 Degree Car Parking” - Jeevabharathi, S. (International Journal of Psychosocial Rehabilitation, 2019)
Modern development and economical progression of Indian society resulted in increase of cars on rods. Due to space constraints, car parking is the major problem faced in most parts of the country. Present study aims for development of a system to reduce the turning radius of a car. The indigenously developed system consists of Ackerman steering and chain drive mechanism with arrangement of the various kinematics links. In this system at first vehicle is stopped and wheels are then turned in the required direction with the help of steering system. It has turning radius nearly equal to negligible of the length of car itself. This system can be useful in better parking, traffic jam, back turning on narrow roads, etc.